2013
DOI: 10.1111/cpr.12034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of Lycoris aurea agglutinin‐induced apoptosis and G2/M cell cycle arrest in human lung adenocarcinoma A549 cells, both in vitro and in vivo

Abstract: LAA triggers G2 /M phase cell cycle arrest via up-regulating p21expression as well as down-regulating cdk-1cyclinA singling pathway, and induces apoptotic cell death through inhibiting PI3K-Akt survival pathway in human lung adenocarcinoma A549 cells. While LAA has no significant cytotoxic effect toward normal human embryonic lung fibroblast HELF cells, and moreover, LAA could amplify the antineoplastic effects of cisplatin toward A549 cells. Lastly LAA also bears anti-cancer and apoptosis-inducing effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The lectin was found to be inactive against the HeLa or p53-deficient Hep3B cell lines at all concentrations and for the entire duration studies (Figure 2). This finding is consistent with the earlier reported variation in the anti-proliferative potential of a variety of lectins with tumor cell lines as a function of their doses [19,21,22].…”
Section: In Vitro Anti-proliferative Potential Of Ael On Human Tumor supporting
confidence: 93%
See 1 more Smart Citation
“…The lectin was found to be inactive against the HeLa or p53-deficient Hep3B cell lines at all concentrations and for the entire duration studies (Figure 2). This finding is consistent with the earlier reported variation in the anti-proliferative potential of a variety of lectins with tumor cell lines as a function of their doses [19,21,22].…”
Section: In Vitro Anti-proliferative Potential Of Ael On Human Tumor supporting
confidence: 93%
“…FACScan flow cytometry was performed as previously described [21]. The percentages of cells at different cell cycle phases, or those that were undergoing apoptosis, were evaluated using Calibur FACScan flow cytometry (Becton Dickinson, Franklin Lakes, NJ, USA).…”
Section: Cell Cycle Measurementmentioning
confidence: 99%
“…The degrees of antiproliferation against human carcinoma cell lines resulting from treatments were evaluated by the MTT assay, and the growth inhibitory rate was expressed as the percentage of the total cells compared with the negative control after 72 hours treatment. Studies showed that a number of Amaryllidaceae alkaloids and their derivatives exhibited remarkable antiproliferative activities89104145. Our results in Table 2 also displays that hippeastrine, [2] benzopyrano [3,4] indole skeleton based lycorenine-type alkaloids, exhibited distinct dose-dependent antiproliferative activities against HT-29 and Hep G2 cells with the IC 50 values at 3.98 ± 0.29 μg/mL and 11.85 ± 0.20 μg/mL, as compared to that of camptothecin at 1.47 ± 0.07 μg/mL and 3.17 ± 0.56 μg/mL, 5-FU at 2.92 ± 0.48 μg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the diverse pharmacological activities, such as anticancer, antimalaria, antifungal, neuroprotective effects, acetylcholinesterase and butyrylcholinesterase-inhibitory activity4567, these alkaloids have attracted a great deal of attentions in modern medical societies. Furthermore, some AAs exhibited significant anticancer effects and were very promising in the treatment of various cancers8910.…”
mentioning
confidence: 99%
“…FACScan flow cytometry assays were performed as previously described [12] . The percentages of the cells at different cell cycle phases or those that were undergoing apoptosis were evaluated by Calibur FACScan flow cytometry (Becton Dickinson, Franklin Lakes, NJ, USA).…”
Section: Cell Culturementioning
confidence: 99%